Progressive Legal Approach In The Reconstruction Of Criminal Sanctions For Corporations Involved In Corruption - Muhammad Nurohim (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2025)
Corruption crimes committed by corporations have become a serious threat to the economy and public trust. The research method used is normative juridical with an approach to laws and regulations, concepts, and cases. The results of the study show that criminal sanctions for corporations are still formalistic and lack a deterrent effect. However, the corporate criminal sanctions system in corruption cases still has various weaknesses, one of which is the lack of an optimal state financial recovery mechanism. In many cases, even though companies are sentenced to fines, the funds from corruption that have been misused are not fully refundable. This is due to several factors, such as weak regulations related to asset recovery, difficulty in tracking the flow of funds that have been laundered, the length of the legal process, and the abuse of legal procedures by corrupt actors. This weakness has a direct impact on increasing state losses, weakening the deterrent effect for corporations, and decreasing public trust in the legal system. To address this problem, stricter legal reforms are needed in terms of asset seizure and recovery, increased international cooperation in tracking corruption proceeds, and the use of technology in financial investigations. By strengthening the state's financial recovery mechanism, it is hoped that corruption in the corporate sector can be suppressed more effectively, and state finances can be restored optimally